Memorias (Editorial Correo del Orinoco CaracasVE, 2011)
Presents the report of the third Conference of Heads of State of the 33 countries of Latin America and the Caribbean which saw the formation of CELAC, whose objective is to deepen the integration and political, economic, social and cultural unity among its members and to establish effective means of joint action for the promotion of sustainable development in the region.
Keywords: REGIONAL ORGANIZATIONS